How might gender norms mediate the benefits of higher coffee production in Uganda? - Doan, Miki; Hoffmann, Vivian (International Food Policy Research Institute, 2021)
Expanding coffee exports is a major goal of Uganda’s government. By focusing on this high-value crop, almost all of which is sold to higher-income countries, Uganda hopes to boost farmers’ incomes and increase the country’s foreign exchange earnings as well as its tax base (UCDA, n.d.). The average yield of smallholder coffee farmers in Uganda amounts to just third of the crop’s agronomic potential (Mongoya, 2018). The opportunity to increase yields – and thus the incomes of some of the world’s poorest farmers – by improving agronomic practices has spurred major philanthropic investment in coffee agronomy training in Uganda. However, gender norms and related constraints may affect how coffee income is distributed within households, and in this way erode the benefits this income brings to rural populations. In many settings, men have traditionally taken the lead role in production of cash crops grown for sale, while women have managed crops grown purely or primarily for subsistence (World Bank, FAO and IFAD, 2009). In this note, we describe results from the baseline survey of an impact evaluation of the Uganda Coffee Agronomy Training (UCAT) program, which aims to train 60,000 smallholder coffee growers over four years. For each cohort of farmers, the program lasts approximately two years, and is delivered through 22 training sessions held monthly for 11 months of the year.